Does capital punishment deter crime? - Keyzer, Amy Marcaccio (At issue, 2009)
The deterrent effect of the death penalty is supported by evidence / Paul G. Cassell -- The deterrent effect of the death penalty is a myth / Jesse L. Jackson Sr., Jessie L. Jackson Jr., and Bruce Shapiro -- Consistent and swift application of the death penalty reduces murder rates / Wesley Lowe -- Deterrence studies of the death penalty are not grounded in science / Jeffrey Fagan -- An effective death penalty protects the community from criminals / Kent Scheidegger -- The death penalty can be a counter-deterrent to crime / Amnesty International -- The death penalty saves lives / William Otis -- The death penalty keeps Americans safe from terrorist threats / George W. Bush -- The death penalty hinders the fight against terrorism / American Civil Liberties Union -- Capital punishment may deter some terrorists / Joanna Shepherd -- The death penalty encourages terrorism / Thomas McDonnell -- Capital punishment maintains law and order / Mufti Zubair Bayat -- Modern societies do not deter crime with capital punishment / Chris Patten for the European Union -- Capital punishment does not make nations safer / Paul Simon -- The Islamic world must reexamine capital punishment / Tariq Ramadan -- The United States must reconsider the death penalty / Richard C. Dieter -- Executions send a strong deterrent message / Peter Ryan -- Executions perpetuate the cycle of violence / Peter C. Valenti